Microfluidic Biochip for Studying Cellular Response to Non-homogeneous DC Electric Fields. (2017) - Rio, Marisa; Bola, Sharanya; Funk, Richard H.W.; Gerlach, Gerald
Abstract: Endogeneous electric fields affect a wide range of cellular functions as migration, wound healing and regeneration. Similar results were observed in the presence of external electric fields. Till date, the phenomenon of electrotaxis was studied only in homogeneous electric field environments. Here, we report on a microfluidic biochip that permits stimulation of cells with stationary, non-homogeneous electric fields, e.g. to simulate the electrical environment during repair processes such wound healing.